Evaluasi Efektivitas Manajemen Pembelajaran Guru Produktif Otomotif SMK - Roni Elistanto; Achadi Budi Santosa; Fitri Nur Mahmudah (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
This study aims to determine (1) the quality of learning materials for automotive productive teacher theory; (2) Preparation and planning of automotive productive teacher learning; (3) Synchronization of theoretical learning with productive teacher practice learning (4) Supervision and follow-up after the evaluation of productive teacher learning. This type of research is an evaluation with a descriptive approach. This research was conducted at SMK Muhammadiyah 1 Moyudan. The respondents were students of automotive engineering expertise programs, all automotive productive teachers, and school principals. The evaluation model used is the Goal Oriented Evaluation Model, which is an evaluation which is oriented towards the objectives of the automotive productive teacher learning management program. Data collection techniques by questionnaire, interview, observation, and documentation. The validity of the instrument through the help of a competent panel. The results showed: (1) The quality of automotive productive teacher learning materials in SMK Muhammadiyah 1 Moyudan was effective. (2) Preparation and planning of learning of automotive productive teachers in SMK Muhammadiyah 1 Moyudan effectively. (3) Synchronization of theoretical learning with learning practices of automotive productive teachers in SMK Muhammadiyah 1 Moyudan effectively. (4) Supervision and follow-up after the evaluation of the learning of automotive productive teachers of SMK Muhammadiyah 1 Moyudan is effective.